(untitled) (Archives of Criminology, 1998)
Burglary is a serious offense which particularly affects the victim. It often has more one victim, and its effects react on ihe entire family and broader community. For the victim, its important element is not only the loss of and possibly damage to property, but also violation of privacy and of the related feeling of safety. The survey discussed in the paper was conducted in 6 cities in the following countries: Germany - Monchengladbach; Poland - Warsaw and Lublin; Hungary - Miskolc; and United Kingdom - Plynouth and Salford. Discussed here will be mainly the findings obtained in Warsaw and Lublin, and data from the rest of the sample will be referred to on some issues only. The survey focused on the following issuess: 1/ circumstances of the offense and losses suffered by the victims; 2/ respondents’ attitudes to the police and appraisal of police work in their case; 3/ assistance received, self-organization, steps undertaken by the victims to prevent further burglaries; 4/ respondents’ feelings, their reactions to the offense and persistence of those reactions. The survey based on data from interviews with victims of burglary and on information obtained from the police (the questionnaire was developed by the designer and head of the project, Prof. R.I. Mawby and contained some questions from the British Crime Survey Questionnaire of 1984, 1988, and l992). Sampled in each city selected for the project were 400 reported cases of burglary; interviews were conducted in a half of those cases (200 burglaries) on two occassions, that is at least 6 to 8 weeks and 16 to 18 weeks after the date burglary was reported. As was shown by comparison of data on the socio-demographic situation of victims of burglary in different countries, variables such as age, structure of family, or material or housing situation significantly differentiate individual national samples (e.g. persons living alone were much fewer in Poland as compared to Hungary and the United Kingdom). The circumstances of burglary, losses suffered and anti-burglary protection measures shape differently in different countries. In the United Kingdom, the number of burglaries committed during the night while the victims were at home and asleep was twice as big as in Poland and Germany. On some points, however, no differences were found. About a half of respondents in all countries said that some of the objects stolen during the burglary were to them of sentimental value. Besides, property stolen most often throughout the sample was electronic equipment. Polish respondents were below the average as regards special protective measures. For example, a slight proportion only had alarm devices installed, and a mere one-third had taken out an insuranie policy. Due to high costs of insurance in Poland, the insurance sum was low as a rule and seldom corresponded with the actual value of equipment. As a result, Polish respondents could not get compensation from the insurance company; when compensation was paid, the loss actually suffered was hardly made up for. Interestingly, though, the taking out of insurance was related neither to respondent’s level of education nor to his self-appraised material situation. Polish respondents’ attitude to the police and opinion on police work tended to be more critical compared to the rest of the sample. Criticized were many aspects of police work in cases of burglary. Polish respondents stated more often that the police had arrived too late, ignored their suggestions as to possibly identity of the burglars, and failed to interrogate persons they indicated. A vast majority of Polish respondents believe that the police failed to inform them properly about the state of investigation. Fewer Polish victims of burglary are also satisfied with the way in which the police conducted the investigation in their case (about 20% compared to about 75% of British and Hungarian respondents). Policemen enjoy a lower prestige among Polish victims. Social perception of the police depends on their treatment of the victim but also on the national tradition, previous experiences with police forces being used by the authorities to perform political tasks, the image of the force created by the media etc. In view of the more critical opinion on the police found among Polish respondents, it is inieresting to find out whether such opinion has any objective grounds, that is whether the proportion of offenders detected in Polish cases was lower compared to the rest of the sample. The answer is no. In cases of burglary, detectability rate was low throughout the sample and Poland was by no means inferior in this respect. Polish victims’ tendency to be the most critical of all towards police work may have a number of reasons. It may be related to actually greater shortages of the force (e.g. inferior equipment); to a greater pain involved in losses suffered by Polish victims; or to society’s critical attitude towards the police fixed under the past regime. On the grounds of our data, it would be difficult to select any of the above three explanations. Considering the reasons of Polish respondents’ critical attitude towards the police, one can hardly ignore the fact that with a growth in both crime and thę social sense of threat in the country, also society’s expectations and demands of the police have gone up. As we know, burglary causes not only material losses but also psychological effects which tend to persist for a long time in many victims. Inquired about in the survey were respondents’ first reactions to burglary; the persistence of those reactions; reactions of their family members; and the aspect the victims considered the worst of all in their experience of burglary. As follows from the findings, the psychological effects of burglary suffered by the victims are similar in all countries in the sample. Most respondents felt depressed, and this frame of mind persisted in onefourth of the sample. The worst experience mentioned most often was material loss (which frequently amounted a loss of possessions that had taken a person’s lifetime to amass); worsening of the living conditions; and in many cases the accompanying sense of harm and injustice. Another worst experience mentioned was invasion of privacy, a loss of trust in one’s fellow men, and helplessness. Persons who consider themselves the most , affected” by burglary among Polish respondents are those calling themselves not too well-off, the not insured, and women rather than men. Compared to the rest of the sample, British respondents feel less affected by burglary; however, burglary was found to affect victims in a similar way irrespective of the country. Interestingly, the frequency of victims’ psychological reactions followed the same pattern throughout the sample. Anger ranked first, followed by shock, anxiety, sleep disorders, and crying. Burglaries examined within the Polish sample affected a greater number of persons compared to those committed in the remaining countries: Polish households that were burgled were bigger. We also strove to find out whether respondents felt threatened with crime. Such sense of threat was more intense in Polish compared to Hungarian and British respondents. The system of assistance to victims was the best in terms of organization and functioning in United Kingdom followed by Germany, Hungary and Poland. The situation of Polish victims of burglary proved the most unfavorable as regards the possibility of getting both compensation for material losses and assistance from competent institutions. As opposed to the rest of the sample, Polish respondents were less often satisfied with the way in which the police handled their case and much more critical towards police work. The findings show that, in Poland in particular, the insurance system has to be reconsidered and differently regulated, and there is an urgent need for a systemic and coordinated program of comprehensive assistance to victims. The more critical opinion on police work found in Polish respondents also suggests that the treatment of victims by the police in Poland requires a thorough analysis.